Studies of CDK 8/19 inhibitors: Discovery of novel and selective CDK8/19 dual inhibitors and elimination of their CYP3A4 time-dependent inhibition potential. Issue 12 (15th June 2017) - Fujimoto, Jun; Hirayama, Takaharu; Hirata, Yasuhiro; Hikichi, Yukiko; Murai, Saomi; Hasegawa, Maki; Hasegawa, Yuka; Yonemori, Kazuko; Hata, Akito; Aoyama, Kazunobu; Cary, Douglas R.
Graphical abstract: Abstract: In this article, synthetic studies around a pyridylacrylamide-based hit compound (1 ), utilizing structure-based drug design guided by CDK8 docking models, is discussed. Modification of the pendant 4-fluorophenyl group to various heteroaromatic rings was conducted aiming an interaction with the proximal amino acids, and then replacement of the morpholine ring was targeted for decreasing potential of time-dependent CYP3A4 inhibition. These efforts led to the compound4k, with enhanced CDK8 inhibitory activity and no apparent potential for time-dependent CYP3A4 inhibition (CDK8 IC50 : 2.5 nM; CYP3A4 TDI: 99% compound remaining). Compound4k was found to possess a highly selective kinase inhibition profile, and also showed favorable pharmacokinetic profile. Oral administration of4k (15 mg/kg, bid. for 2 weeks) suppressed tumor growth (T/C 29%) in an RPMI8226 mouse xenograft model.